Migration and perinatal mental health in women from low‐ and middle‐income countries: a systematic review and meta‐analysis. (20th June 2016) - Fellmeth, G; Fazel, M; Plugge, E
Abstract : Background: Migrant women are at risk of perinatal mental disorders due to stressors experienced before, during and after migration. Objectives: This systematic review and meta‐analysis summarises the prevalence, associated factors and interventions for perinatal mental disorders in migrant women from low‐ and middle‐income countries (LMIC). Search Strategy: We systematically searched nine electronic databases and the grey literature using a predefined search strategy. Selection Criteria: Studies were included if they assessed pregnant or postpartum migrants from LMIC, used a structured tool and a case‐control, cross‐sectional, cohort or intervention study design. Data collection and analysis: Data was double‐extracted. We calculated pooled prevalence of depression and weighted mean anxiety and depression scores. We calculated crude odds ratios from risk factor studies and summarised intervention studies descriptively. Main results: Forty studies were identified from 10 123 references. Pooled prevalence was 31% [95% condidence interval (CI) 23%–40%] for any depressive disorder and 17% (95% CI 12–23%) for major depressive disorder. Previous depression and lower social support were associated with perinatal depression. There were insufficient data to assess the burden of anxiety, post‐traumatic stress disorder or psychosis in this population. Conclusions: One in three migrant women from LMIC experiences symptoms of perinatal depression. Social support is an important protective factor. Evidence on LMIC women relocating to other LMIC is lacking. Given the adverse consequences of perinatal mental illness on women and their children, further research in low‐resource settings is a priority. Tweetable Abstract: One in three migrant women from low‐ and middle‐income countries has symptoms of perinatal depression. Tweetable Abstract: One in three migrant women from low‐ and middle‐income countries has symptoms of perinatal depression.